2021
DOI: 10.1007/s11089-021-00979-w
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Meaning in Life Through Continuing and/or Transforming the Bond to a Deceased Spouse in Late Life

Abstract: Bereavement is an ongoing process of negotiation and meaning-making in which widows and widowers make sense of the changed nature of their relationship with their deceased spouse. We analyzed the experiences of meaning in life among older widows and widowers (aged 65+) using interpretative phenomenological analysis (IPA; see Smith et al. in Interpretative phenomenological analysis: Theory, method and research, Sage, 2009), with the following question: How do widows and widowers search for meaning through conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
3
1
Order By: Relevance
“…All those who wrote on spiritual space in the data for this study seemed to be rather religious and their ritual space included religious elements such as a candle or silent moment, as well as such memorial elements as a picture of the deceased. In this aspect also, the findings of this study differ from previous research on memorial rituals, according to which non-religious people participated in various post-mortem rituals as well (Mathijssen 2018;Vähäkangas et al 2021;Wojtkowiak and Venbrux 2009). These self-created ritual spaces characterized multi-dimensional understandings of the deathscape, but further research is needed to better ascertain what these spaces mean, and if they are only individual spaces or if participants find them to be shared spaces.…”
Section: Discussion: Physical Virtual and Spiritual Spacescontrasting
confidence: 91%
“…All those who wrote on spiritual space in the data for this study seemed to be rather religious and their ritual space included religious elements such as a candle or silent moment, as well as such memorial elements as a picture of the deceased. In this aspect also, the findings of this study differ from previous research on memorial rituals, according to which non-religious people participated in various post-mortem rituals as well (Mathijssen 2018;Vähäkangas et al 2021;Wojtkowiak and Venbrux 2009). These self-created ritual spaces characterized multi-dimensional understandings of the deathscape, but further research is needed to better ascertain what these spaces mean, and if they are only individual spaces or if participants find them to be shared spaces.…”
Section: Discussion: Physical Virtual and Spiritual Spacescontrasting
confidence: 91%
“…Specifically, instrumental PSS relies on the adequacy of tangible support, which is primarily associated with biological functions and physical health, as a coping resource (Uchino, 2006). By contrast, emotional PSS constitutes companionship, which not only mitigates loneliness and isolation but also promotes psychosocial resources, including self-esteem, self-efficacy, and a sense of meaning in life, among people experiencing bereavement (Cacciatore et al, 2021; Holt-Lunstad, et al, 2015; Thoits, 2011; Vähäkangas et al, 2021; Wright, 2021). Older bereaved people might benefit more from psychosocial resources (i.e., emotional PSS) than from other resources, because according to Erikson’s theory of psychosocial development, older adults are triggered to develop ego integrity to feel a sense of fulfillment and life success, as their functional abilities decline (Perry et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Next, the present study revealed that consistently high emotional PSS trajectory had a considerably stronger protective effect on mortality risk for a widow or widower than did consistently high instrumental PSS trajectory. In collectivistic societies, such as Taiwanese society (Insights, 2022), people tend to consider their spouse as an integral part of their social network and therefore develop emotional dependence on their spouse; thus, an older individual with a deceased spouse may be faced with the challenge of restoring meaning in their life, which might require extensive psychosocial resources (Anusic & Lucas, 2014; Vähäkangas et al, 2021). Therefore, persistent emotional social support for widows and widowers can promote a robust sense of social connection and safety and a perceived attachment to society among them, which reduces their mortality risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(e.g., Martinez-Calderon et al, 2023). The procedure for the empirical study involved articles based on facts that were either observable or obtained through experiments or interventions (e.g., Vähäkangas et al, 2021).…”
Section: Methodsmentioning
confidence: 99%